Exploring the therapeutic potential of edible mushrooms: antioxidant and anti-inflammatory properties of Agaricus bisporus and Pleurotus ostreatus extracts - Shrivastava, Preeti; Verma, Ayushi; Ali, Nirali; Patel, Sanjana; Limaye, Rashmi; Puri, Payal (Brazilian Journal of Science, 2026)
This study comparatively analyzed the protein profiles, antioxidant potential, and anti-inflammatory activities of Agaricus bisporus (button mushroom) and Pleurotus ostreatus (oyster mushroom). Proteins were extracted, purified via ammonium sulfate precipitation and dialysis, and quantified using the Lowry assay. SDS-PAGE analysis revealed distinct protein bands, particularly in the 11-17 kDa range, within fractions exhibiting the most promising bioactivities. Both mushroom species demonstrated significant total antioxidant capacity (TAC) via the phosphomolybdate assay, with notably high values observed in the P. ostreatus 30% (1.52 mg mL AAE-1), P. ostreatus 70% (0.85 mg mL AAE), and A. bisporus 70% (1.6 mg mL AAE-1) precipitation fractions, as well as crude extracts. For anti-inflammatory activity, evaluated by red blood cell (RBC) hemolysis inhibition, all extracts and fractions showed anti-hemolytic effects. The P. ostreatus 70% (72.15% inhibition), P. ostreatus 30% (69.62% inhibition), and A. bisporus 70% (68.35% inhibition) precipitation fractions displayed the highest efficacy. While oyster mushroom crude extract yielded a higher protein concentration (9.516 mg mL-1) than A. bisporus mushroom (6.516 mg mL-1), the study's focus remained on the functional activities of specific fractions. This research underscores the significant potential of both A. bisporus and P. ostreatus as natural sources of antioxidants and anti-inflammatory agents. The strong correlation between these high bioactivities and the presence of specific protein bands, particularly in the 11-17 kDa range within the most active fractions, emphasizes the crucial role of their protein components. Further investigation is warranted to isolate, characterize, and elucidate the mechanisms of action of these specific bioactive proteins for potential applications in functional foods, nutraceuticals, and pharmaceuticals.